HYBRID ON-GRID SOLAR PANEL DENGAN ENERGY STORAGE PADA INSTALASI LISTRIK ENERGI TERBARUKAN PONDOK PESANTREN AL ANWAR BANTUL - prabowo, harry (Jurnal Riset Daerah, 2023)
Energy storage is a means of storing energy, especially solar energy which has been converted into electrical energy and stored in a device commonly referred to as a battery or accumulator. The battery in question is having a voltage and electric current as volts and ampere hours, as well as the characteristics of Deep of Discharge (DoD) in rechargeable battery operation. The Hybrid On-Grid Inverter Solar Panel at the Al Anwar Islamic Boarding School electrical installation, Bantul, Yogyakarta is a hybrid on-grid inverter with solar panels operating in 2019 connected to help supply the cottage's electric power from PLN. If the electric power supply from PLN is off, then the on-grid solar panel inverter hybrid does not immediately take over the PLN electricity supply. This hybrid on-grid inverter solar panel, has the function of working to help supply electricity from PLN to the electrical installations of Islamic boarding schools by utilizing sunlight when it shines bright enough. At night the electricity supply for the cottage is not only served from the PLN electricity network but is assisted by the supply of electric power from the installed energy storage. Before energy storage was installed, the electricity supply to the cottage was only served during the day or when there was sun by a hybrid on-grid inverter solar panel together with electricity supply from PLN. In 2022, Pondok will receive electric power supply from a hybrid on-grid inverter solar panel with energy storage along with the electricity supply from PLN during the day and night. Thus PLN supplies electricity to be lighter for the Pondok both during the day and at night. The installed Hybrid On-Grid Inverter has a capacity of up to 5000 Volt Ampere, 2 units of Energy Storage or LiFePO4 Batteries with each unit having a capacity of 48 Volts 100 Ampere Hours, and the Solar Panel or Photovoltaic installed is Monocrystalline 5 x 400 Watt Peak so that the capacity a total of 2000 Watt Peaks. Meanwhile, the electric power line from PLN to the Pondok Pesantren's electrical installation has a capacity of 3500 Volt Ampere.